Optimization of the Newa-Based Tourism Development Model (Nature, Ecotourism, Wellness, and Adventure) Through the Eco-Wellness Tourism Concept Approach - Lastiani Warih Wulandari (Eduvest - Journal of Universal Studies, 2024)
NEWA (Nature, Ecotourism, Wellness Tourism, and Adventure) is a new trend developing in the tourism industry in the era of the passing of the Covid-19 pandemic. The pattern of NEWA concept development that tends to be fragmentative causes the exploration of each concept to be more limited. Efforts to optimize NEWA are carried out through blending concepts in the frame of eco-wellness tourism. Therefore, an effort is needed to formulate the concept of eco-wellness tourism, as well as how to apply the concept in the implementative realm. This research uses a descriptive qualitative research approach, through the Forum Group Discussion (FGD) technique involving cross-disciplinary experts. Eco-wellness tourism combines healthy tourism destinations in wellness tourism with an environmental conservation orientation typical of ecotourism such as traditional spas, herbal concoctions, gastronomy, aromatherapy, and hypnotherapy as its activities, which are packaged in the concept of interactive activities with nature such as thematic camping, adventure, exploration, and rural tourism.